MANDAILING LANGUAGE MAINTENANCE IN KELURAHAN SUDIREJO II MEDAN - Nisma Zuri; Sumarsih Sumarsih; Edy Setia (Universitas Negeri Medan, 2018)
This study deals with Language Maintenance in Kelurahan Sudirejo II Medan. The objectives of the study are (1) to describe out the factors affecting Mandailing Languagein Kelurahan Sudirejo II Medan (2) to elaborate how Mandailingnese maintain the Mandailing Languagein Kelurahan Sudirejo II Medan, and (3) to reason for the manners or way by which they maintain Mandailing Languagein Kelurahan Sudirejo II Medan. The method of this study was descriptive qualitative research. The participants were twenty Mandailing people who live in Kelurahan Sudirejo II Medan. The data were taken from questionnaire and interview as instrument. Questionnaire was applied to collect the data about the factors affecting the Mandailing Language maintenane and strategies in maintaining ML. While the interview was applied to get data about the reason of Mandailing people maintain Mandailing Language. The data were analyzed by using Miles and Huberman matrix (1994). This research found the following results (1) There are seven factors affecting Mandailing Languagemaintenance in Kelurahan Sudirejo II Medan such as: Use of language in family (intermarriage and intermarriage), visiting homeland, use of the language in neighborhood domain, ethno linguistic vitality, living together in an area, use of the language in religion and practice of traditional ceremony. (2) to maintain Mandailing Language, the Mandailing people in Kelurahan Sudirejo II Medan conducted strategies like: Family language policy, using Mandailing Languagein daily life, using Mandailing Languagein social meeting or religious, using Mandailing Languagein cultural activity. (3) the reasons why the Mandailing people maintain the language are: they were proud being Mandailing people and speak Mandailing language and Mandailing Languageshows their identity as Mandailing people. Keywords: Language maintenance and Mandailing.